Avaliação do potencial antimicrobiano e leishmanicida de materiais orgânicos derivados da base de Schiff N,N-bis’(Salicilideno)-1,2-fenilenodiamina - Soriano, Bianca (Universidade Federal de São Carlos, 2017)
Bacteria and fungi are the main etiological agents potentially causing health care-related infections and the fourth leading cause of death, according to the WHO. Parasitic agents such as Leishmania infantum chagasi, the causative agent of leishmaniasis, neglected and endemic disease, have treatments that are not always eﬀective and have serious side eﬀects. Resistance to antibiotics, antimycotics and leishmanicides, has increasingly induced bioprospecting and synthesis of new substances with pharmacological properties. The Schiﬀ bases, especially those derived from the N, N’-bis (salylcilidene) -1,2-phenylenediamine linker, also known as Salofen, have been studied in order to demonstrate the physical, chemical and biological properties due to Variety of potential technological applications. The objective of this work was to evaluate the biotechnological potential of the Schiﬀ N, N’-bis (salylcilidene) -1,2-phenylenediamine (Salofen) base derivative in relation to the antimicrobial and leishmanicidal activity. Agar diﬀusion techniques and microdilution assays were used for bacterial and yeast studies, and the colorimetric method with Alamar Blue® for Leishmania tests at 24 and 48 hours. Inhibition halos were observed for all microorganisms tested, with the highest mean halos (30 mm) for Candida albicans. Dilution assays have shown promising results, with inhibition rates above 90%, emphasizing better Gram-negative efciency. The leishmanicidal eﬀect was also observed with IC50 at 1.06 mg.mL−1 at 24 hours and 0.66 mg.mL−1 at 48 hours. Thus, the data collected suggest that the Schiﬀ base tested has an antimicrobial and leishmanicidal potential of the compound studied, suggesting a biotechnological application.
Evaluation of antimicrobial and leishmanicide potential of organic materials derived from the Schiff base N,N-bis'(Salicylidene)-1,2-phenylenediamine
Keywords: Microrganismos; Leishmania; Salofen; Ensaios de microdiluição; Microorganisms; Microdilution assays.; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA; CIENCIAS BIOLOGICAS::PARASITOLOGIA::PROTOZOOLOGIA DE PARASITOS